Correlation between Carcinoembryonic Antigen (CEA) Levels and Colorectal Carcinoma Stage Using Computed Tomography (CT) scan : a Study at Dr. Hasan Sadikin Central General Hospital Bandung 2019 - Ristaniah D. Soetikno*,Tri Lestari, Leni Santiana, Dian Komala Dewi (Innovative Journal of Medical and Health Sciences, 2020)
Background : Colorectal carcinoma (CRC) ranks as the third most common cancer and the fourth most lethal cancer among other malignancy around the world. Carcinoembryonic antigen (CEA) is one of the most common tumor marker used in CRC for predicting prognosis and therapeutic response. Several studies reported correlation between CEA level and the clinical stage of CRC. The determination of clinical stage has an important role in management planning of CRC. Determination of the CRC clinical stage using Computed Tomography (CT) scan demonstrates good sensitivity and specivicity rates. Objective : To review the correlation between CEA level and the stage of CRC using CT scan. Methods : This study was of retrospective observational analytic study with cross sectional design. Simple random sampling was used to collect data from available medical records and the data were analyzed statisticaly using Spearman test. Results: There were 40 subjects, 24 were men (60%) and 16 women (40%). The average age of the patients was 55,0210,84 and ranged from 28 to 79 year old. The highest average CEA level was found in stage IV with a value of 351.26 + 833.65 ng/ml and the lowest average CEA level was in stage I with a value of 1.53 + 2.04 ng/ml. The results of the statistical test with Spearman gave a p value of 0.0001 (p <0.05) and a correlation coefficient (R) of 0.588 showed a significant correlation between CEA level with clinical stage with a positive correlation direction and moderate correlation strength. Conclusions : There is a significant correlation between CEA level with clinical stage of colorectal carcinoma using CT scan examination in Dr. Hasan Sadikin General Hospital. Key words: Carcinoembryonic antigen (CEA)–clinical stadium–colorectal carcinoma–Computed Tomography (CT) scan.